Strategic alternatives for increasing the enterprise's financial potential - Мyroslava Zabediuk; Іlona Yatsuk (Економічний форум)
The article is devoted to the study of the peculiarities of the formation of strategic alternatives in the direction of increasing the enterprise's financial potential. It is noted that in the process of developing the enterprise's financial strategy, it is necessary, firstly, to ensure its compliance with the enterprise's financial policy as a whole; secondly, the enterprise's financial strategy should be aligned with its basic corporate strategy. Also, it should be taken into account that a key factor in the development of the enterprise's financial strategy is the need for it to match the enterprise's internal potential. The main strategic stages of increasing the enterprise's financial potential have been formed. The basic financial strategies in the aspect of increasing the enterprise's financial potential are considered: the strategy of forming financial resources, the structural financial strategy and the strategy of ensuring financial security. The formation and implementation of the enterprise's basic financial strategies must be consistent with the situation and development trends of the market in which the enterprise operates. At the same time, it is also necessary to take into account risk factors at the state level and global threats. Along with the basic financial strategies, functional strategies related to the formation and improvement of the efficiency of the use of the enterprise's financial potential are considered. A classification of functional strategies, systematized according to individual approaches, is given. In the process of choosing strategic alternatives for increasing the enterprise's financial potential, each enterprise must take into account the specifics of its activity, the influence of a combination of factors, etc. A successful choice and combination of strategies for increasing financial potential leads to the minimization of risks, the growth of activity efficiency, the improvement of financial stability and the provision of competitive positions of the enterprise The article is devoted to the study of the peculiarities of the formation of strategic alternatives in the direction of increasing the enterprise's financial potential. It is noted that in the process of developing the enterprise's financial strategy, it is necessary, firstly, to ensure its compliance with the enterprise's financial policy as a whole; secondly, the enterprise's financial strategy should be aligned with its basic corporate strategy. Also, it should be taken into account that a key factor in the development of the enterprise's financial strategy is the need for it to match the enterprise's internal potential. The main strategic stages of increasing the enterprise's financial potential have been formed. The basic financial strategies in the aspect of increasing the enterprise's financial potential are considered: the strategy of forming financial resources, the structural financial strategy and the strategy of ensuring financial security. The formation and implementation of the enterprise's basic financial strategies must be consistent with the situation and development trends of the market in which the enterprise operates. At the same time, it is also necessary to take into account risk factors at the state level and global threats. Along with the basic financial strategies, functional strategies related to the formation and improvement of the efficiency of the use of the enterprise's financial potential are considered. A classification of functional strategies, systematized according to individual approaches, is given. In the process of choosing strategic alternatives for increasing the enterprise's financial potential, each enterprise must take into account the specifics of its activity, the influence of a combination of factors, etc. A successful choice and combination of strategies for increasing financial potential leads to the minimization of risks, the growth of activity efficiency, the improvement of financial stability and the provision of competitive positions of the enterprise